2011
DOI: 10.1088/1674-1056/20/7/076104
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic simulation of site preference, Curie temperature, and lattice vibration of Nd2Co7−xFex

Abstract: Qian Ping() a) † , Liu Jiu-Li ( ) a) , Hu Yao-Wen( ) b) , Bai Li-Jun( ) a) , and Shen Jiang( ) a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…[1][2][3][4] Recently, Chen et al have performed serial theoretical studies on the properties of the rare earth compounds. [5][6][7][8] In the present work, atomistic studies on the structural and vibrational properties of Co-based rare earth compounds RCo 2 and Nd 1Àx R x Co 2 (R ¼ rare earth) are performed by using inverted interatomic pair potentials. Emphasizing the statistical analysis of the phonon density of states (DOS), the Debye temperature of RCo 2 and Nd 1Àx R x Co 2 is also evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Recently, Chen et al have performed serial theoretical studies on the properties of the rare earth compounds. [5][6][7][8] In the present work, atomistic studies on the structural and vibrational properties of Co-based rare earth compounds RCo 2 and Nd 1Àx R x Co 2 (R ¼ rare earth) are performed by using inverted interatomic pair potentials. Emphasizing the statistical analysis of the phonon density of states (DOS), the Debye temperature of RCo 2 and Nd 1Àx R x Co 2 is also evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Florio et al [2] reported on the first structurally characterized ternary boride of the Th7Fe3 structure type. In theoretical research, Chen et al have performed studies on the structural properties for the compounds of 1:5-type and their derivative compounds [3][4][5][6][7] from the viewpoint of energy. The method combining interatomic potentials with different crystal structures is a shortcut but effective way to investigate the structural stability and the site preference.…”
Section: Introductionmentioning
confidence: 99%
“…And the inversion method has been applied to ionic crystals, [17] metal-ceramic interfaces, [18] rare earth transition intermetallic compounds, [19] semiconductors, [20] and actinicles intermetallics. [21,22] It is noteworthy that the interatomic pair potential can be strictly acquired to arbitrary-distance neighbor by using Chen's lattice inversion.…”
Section: Introductionmentioning
confidence: 99%